Bare nominals are underspecified for (in)definite meanings, not ambiguous between them - Srinivas, Sadhwi (Proceedings of the Amsterdam Colloquium, 2025)
Definite bare nominals in article-less languages exhibit a more limited distribution than English the in anaphoric contexts. Here, I argue that a comprehensive account of this fact is facilitated by a wherein bare nominals are underspecified for (in)definiteness in episodic contexts, instead of the standard view that they are ambiguous– with the two meanings arising through completely independent means. I discuss how assuming underspecificity in the bare nominals opens up a new type of empirically viable, analytically parsimonious account of their anaphoric variability unavailable under the ambiguity view.